POLITIK HUKUM NASIONAL TERHADAP HUKUM ADAT(STUDI MASYARAKAT HUKUM ADAT REJANG DI BENGKULU) - Teguh, Kayen, Prof. Dr. Khudzaifah Dimyati, Dr. Aidul Fitriciada Azhari, SH., M.Hum (2016)
POLITICAL NATIONAL LAW ON INDIGENOUS (Study of Indigeneous People in Bengkulu Rejang) ABSRACT Teguh Kayen, NIM R100140010, Student of Law Magister Muhammadiyah University of Surakarta In the literature of foreign language are much discussed about customary law of Rejang, system of social life, and custemary law of community govermence of Rejang and jurisprudence in the National legal order that related to customary law, however but all within the scope of the system common law. In Indonesian that has Jurisdiction of civil law, it is still very rare studies that integrating between legal studies of law (the theory of legal positivism) and theory recognition. Political implementation of the law towards customary law can not released from the legal political system of law that has existed in indigenous people at the village level. Legislation which govern about law politics of indogenous people in the village has been arranged in specifically that integrating legal studies of law (the theory of legal positivism) and theory recognition that produce the village law. It should be directed in each role as the rule of law in order to not only be a formality, especially the village with customary law. Because of country worldy from the system law in the village. It teach us about how to apply the legal political system of democracy, the system of implementation of settlement dispute with a fair trial and professionals, as well as how the realization of estimate village which participatory and empowering. Keywords: Political Law, Indigeneous People, Positivism Theory, Theory Recognition.